Strontium Functionalized in Biomaterials for Bone Tissue Engineering: A Prominent Role in Osteoimmunomodulation - You, Jiaqian; Zhang, Yidi; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2022)
With the development of bone tissue engineering (BTE), bio-scaffold materials by adding metallic ions to improve bone healing have been extensively explored in the past decades. Strontium (Sr), a non-radioactive element, as an essential osteophilic trace element for the human body, has received widespread attention in the medical field due to its superior biological properties of inhibiting bone resorption and promoting osteogenesis. As the concept of osteoimmunology developed, the design of orthopedic biomaterials has gradually shifted from "immune-friendly" to "immunomodulatory" with the aim of promoting bone healing by modulating the immune microenvironment through implanted biomaterials. The process of bone healing can be regarded as an immune-induced procedure in which immune cells can target the effector cells such as macrophages, neutrophils, osteocytes, and osteoprogenitor cells through paracrine mechanisms, affecting pathological alveolar bone resorption and physiological bone regeneration. As a kind of crucial immune cell, macrophages play a critical role in the early period of wound repair and host defense after biomaterial implantation. Despite Sr-doped bio-scaffold materials being increasingly investigated, how extracellular Sr2+ guides the organism toward favorable osteogenesis by modulating macrophages in the bone tissue microenvironment has rarely been studied. This review focuses on recent knowledge that the trace element Sr regulates bone regeneration mechanisms through the regulation of macrophage polarization, which is significant for the future development of Sr-doped bone repair materials. We will also summarize the primary mechanism of Sr2+ in bone, including calcium-sensing receptor (CaSR) and osteogenesis-related signaling pathways.